Tetracycline Resistant Vibrio species with tet genes in soil samples from two dumpsites in Port-Harcourt, South-South, Nigeria (African Journal of Biomedical Research, 2023)
With consistent evolutions in the menace of antimicrobial-resistance, there is an ongoing need to continuously grow in understanding the developmental strategies of drug resistant pathogens and possible reservoirs of the resistance determinants. Resistance against tetracycline, a first line anti-cholera drug choice has been reported. With acquisition of resistance in Vibrio, thought to be associated with exchange of extrachromosomal genetic material from closely related species, this study therefore explores the potential role of environmental Vibrio from Rivers State, Nigeria as reservoirs of tetracycline-resistance genes. Soil samples were collected from two dumpsites in Rivers State, Nigeria and processed for the isolation and identification of Vibrio sp according to standard protocols. Identified Vibrio isolates were then screened for the presence of four tetracycline-resistance determinants (tetA, tetB, tetG and tetM) following DNA extraction by boiling. A total of 29.2% of isolates (14/48) possessed at least one of the four tet genes assayed for. For specific occurrence, tetB was the most occurring of the four (14.6%) and tetG the least occurring (2.1%). Both dumpsites had a similar level of occurrence of the tet genes (26.9% and 31.8%), but there was a higher representation (54.5%) of tet genes in isolates obtained from the subsoil than the surface (7.7%). Results indicate a potential role of these environmental Vibrio sp. as reservoirs of tetracycline-resistance genes. The presence of the tetM gene associated with a conjugative transposon adds more risk to this potential. More studies are needed to proffer a better understanding of the risks and relationships present